1997
DOI: 10.1152/ajpheart.1997.273.1.h12
|View full text |Cite
|
Sign up to set email alerts
|

SR Ca(2+)-ATPase activity and expression in ventricular myocardium of dogs with heart failure

Abstract: The purpose of this study was to examine the activity and expression of sarcoplasmic reticulum (SR) Ca(2+)-ATPase in left ventricular (LV) myocardium of dogs with chronic heart failure (HF). LV and right ventricular (RV) tissue specimens were obtained from six normal (NL) control dogs and six dogs with chronic HF (LV ejection fraction, 23 +/- 2%) produced by multiple sequential intracoronary microembolizations. Thapsigargin-sensitive Ca(2+)-ATPase activity was measured in isolated SR membrane fractions prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…43 Interestingly, interventricular differences in RyR2 expression were eliminated, and total RyR2 expression decreased in dogs with arrhythmogenic right ventricular cardiomyopathy. 41 Similarly, Gupta et al 44 found reduced SERCA2a activity and protein levels in LV, but not RV, in dogs with chronic heart failure, eliminating interventricular differences. These data suggest that interventricular differences in Ca 2+ handling are species dependent and can be further regulated by chamber-specific disease-related remodeling.…”
Section: Differences In Ca 2+ Handling and Contractilitymentioning
confidence: 92%
“…43 Interestingly, interventricular differences in RyR2 expression were eliminated, and total RyR2 expression decreased in dogs with arrhythmogenic right ventricular cardiomyopathy. 41 Similarly, Gupta et al 44 found reduced SERCA2a activity and protein levels in LV, but not RV, in dogs with chronic heart failure, eliminating interventricular differences. These data suggest that interventricular differences in Ca 2+ handling are species dependent and can be further regulated by chamber-specific disease-related remodeling.…”
Section: Differences In Ca 2+ Handling and Contractilitymentioning
confidence: 92%
“…17 For thapsigargin-sensitive SERCA2a activity measurements, membrane vesicles were prepared from LV tissue as previously described. 18 SERCA2a activity was determined in the absence and presence of thapsigargin at varying calcium concentration (0.1 to 10.0 mol/L) as previously described 18 and the activity expressed as mol Pi released/min per mg of noncollagen protein.…”
Section: Determination Of Sr Camentioning
confidence: 99%
“…In recent years there has been a great deal of attention paid to intracellular mediators of hypertrophic signaling cascades, and data have been inferred to link some of these proteins and transcription factors to the early development of heart failure. [2][3][4][5][6] To that end, many protein kinases and their substrates that mediate the expression of hypertrophy and progression to heart failure have been relatively well characterized. Much less relative attention has been paid to the protein phosphatases in this regard.…”
mentioning
confidence: 99%
“…[1][2][3][4] This slower decline has been attributed to a decrease in the Ca 2ϩ uptake into the sarcoplasmic reticulum (SR); and particularly with the relative role of phospholamban (PLB) and the SR Ca 2ϩ -ATPase (SERCA). 4,5 Whereas previous work has successfully targeted PLB and SERCA in the investigational treatment of heart failure in mouse, rat, and human myocytes, more recent work has focused on the potential modulators of this system to elucidate the pathophysiologic changes that result in aberrant calcium handling. [2][3][4][5][6] In this issue, Pathak and del Monte et al show that targeted inhibition of protein phosphatase 1 (PP1) by increased activity of its inhibitor, inhibitor-1 in the heart, results in enhanced contractility and is protective against the development of cardiac hypertrophy and heart failure stimulated by hemodynamic load.…”
mentioning
confidence: 99%
See 1 more Smart Citation